Zirconia-supported 12-tungstophosphoric acid as a solid catalyst for the synthesis of linear alkyl benzenes - Devassy, Biju M.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated with zirconia-supported 12-tungstophosphoric acid (TPA) as catalysts. We prepared the catalysts, with different TPA loading (5-20 wt% calcined at 750 degrees C) and calcination temperatures (15 wt% calcined from 650 to 850 degrees C), by suspending hydrous zirconia in a methanol solution of TPA, followed by drying and calcination. These catalysts were characterized by X-ray diffraction, DTG-DTA, FTIR pyridine adsorption, NH3-TPD, and P-31, MAS NMR spectroscopy measurements. The catalyst with optimum TPA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents and characterized by P-31 MAS NMR spectroscopy. The XRD results indicate that TPA stabilizes the tetragonal phase of zirconia. The catalysts show both Bronsted and Lewis acidity, and 15% TPA on zirconia calcined at 750 degrees C shows the highest acidity. P-31 MAS NMR spectra show two types of phosphorous species: one is the Keggin unit and the other is the decomposition product of TPA. The relative amount of each depends on TPA loading, calcination temperature, and the solvent used for the catalyst preparation. Under reaction conditions of 84 degrees C and a benzene/1-olefin molar ratio of 10 (time 1 h), the most active catalyst, 15% TPA, calcined at 750 degrees C, gave more than 98% olefin conversion with selectivity for 2-phenyl octane (53.5%) and 2-phenyl dodecane (47%). (c) 2004 Elsevier Inc. All rights reserved.
Keywords: 12-tungstophosphoric acid; linear alkyl benzene; solvent effect; Zirconia